Kinerja Aparatur Pemerintahan Daerah Kabupaten Batanghari - Etty Siswati; Sumantri Sumantri; Albetris Albetris; Aris Triyono (Universitas Batanghari Jambi, 2021)
The purpose of the Author to make this study is to see how much influence independent variables consisting of Participation (X1), Motivation (X2) and Delegation of Authority (X3) To dependent variables namely Performance (Y) Government Apparatus in Batanghari Jambi District. This research is categorized into descriptive quantitative research and samples from this study as many as 104 respondents. Data collection method is Stratified random smpling with the allocation of 2 respondents per strata. From the research that the authors have done, the results of the partial test for the value (X1) t - count 1,734 greater than degan t - table that is 1.66025, (X2) with a value of t - count 0.421 less than the value of t - table is 1.66025, while (X3) the value t - count 1570 is smaller than the value t - table 1.66025. while the results of simultaneous test (Test F) were found to be F - calculated with a value of 4,789 and a value of F - a table with a value of 2.70 because the value of F - count greater F - table, then the author concluded that Participation, Motivation, Delegation of Authority showed a significant and Positive influence on the performance of government apparatus. And from the Results adjusted R Square obtained a value of 0.99, the author concluded the influence of Participation(X1), Motivation(X2), Delegation of authority (X3) to the Performance of Government Apparatus (Y) by 9.9% and 90.1 % influenced by variables that have not been included in this study.